2014
DOI: 10.1523/jneurosci.5315-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Size and Synchronization of Auditory Cortex Promotes Musical, Literacy, and Attentional Skills in Children

Abstract: Playing a musical instrument is associated with numerous neural processes that continuously modify the human brain and may facilitate characteristic auditory skills. In a longitudinal study, we investigated the auditory and neural plasticity of musical learning in 111 young children (aged 7-9 y) as a function of the intensity of instrumental practice and musical aptitude. Because of the frequent co-occurrence of central auditory processing disorders and attentional deficits, we also tested 21 children with att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
236
3
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(265 citation statements)
references
References 112 publications
17
236
3
9
Order By: Relevance
“…Recent longitudinal studies have observed structural (Hyde et al, 2009) and functional (Seither-Preisler, Parncutt, & Schneider, 2014; Trainor, Lee, & Bosnyak, 2011) music-induced neuroplasticity that corroborates correlational differences between adult musicians and nonmusicians (for reviews, see Herholz & Zatorre, 2012; Münte, Altenmüller, & Jäncke, 2002). Multiple studies have suggested that the neural basis of the reported music-to-other-cognition transfer effects involves enhancement of neural resources shared with general executive cognition; however, they acknowledge that the methods failed to capture sufficient cortical dynamics to describe a more specific mechanism (Moreno et al, 2011; Jentschke & Koelsch, 2009; Patel, 2003).…”
Section: Introductionmentioning
confidence: 60%
“…Recent longitudinal studies have observed structural (Hyde et al, 2009) and functional (Seither-Preisler, Parncutt, & Schneider, 2014; Trainor, Lee, & Bosnyak, 2011) music-induced neuroplasticity that corroborates correlational differences between adult musicians and nonmusicians (for reviews, see Herholz & Zatorre, 2012; Münte, Altenmüller, & Jäncke, 2002). Multiple studies have suggested that the neural basis of the reported music-to-other-cognition transfer effects involves enhancement of neural resources shared with general executive cognition; however, they acknowledge that the methods failed to capture sufficient cortical dynamics to describe a more specific mechanism (Moreno et al, 2011; Jentschke & Koelsch, 2009; Patel, 2003).…”
Section: Introductionmentioning
confidence: 60%
“…Oechslin, Meyer, & Jäncke, 2010;Seither-Preisler, Parncutt, & Schneider, 2014) evidence has been provided that music and language are also partially processed in the same brain regions. Learning a musical instrument also seems to affect learning abilities in general (Serrallach et al, 2016), and musical expertise leads to higher recall, memorisation and imitation ability of foreign language material (Christiner & Reiterer, 2015Fonseca-Mora et al, 2015) stressing that the interconnectivity of both faculties may be one out of many reasons why high achievement in one of the two domains also explains high achievement in the other.…”
Section: Musical Abilities and Phonetic Language Aptitudementioning
confidence: 99%
“…These differences have been attributed to training-related plasticity (Steele et al 2013; Zatorre et al 2012; Klein et al 2014; Imfeld et al 2009; Tavor et al 2013; Sampaio-Baptista et al 2013; Schlegel et al 2012; Draganski et al 2014; Seither-Preisler et al 2014), and to domain-specific aptitudes (Golestani et al 2011; Reiterer et al 2011; Seither-Preisler et al 2014). …”
Section: Introductionmentioning
confidence: 99%